Quo vadis Kita-Beiträge? - C. Katharina Spieß (Wirtschaftsdienst, 2017)
Über die Frage, ob bzw. in welcher Höhe Eltern Beiträge für die Bildung und Betreuung ihrer Kinder in Kindertageseinrichtungen zahlen sollen, wird immer wieder und auch aktuell im Bundestagswahlkampf 2017 diskutiert. In Deutschland unterscheidet sich die Praxis bei der Erhebung der Kita-Beiträge stark auf der Ebene der einzelnen Bundesländer, der Gemeinden und teilweise auch bei den Kita-Trägern. C. Katharina Spieß analysiert die Situation aus einer familien- und bildungsökonomischen Perspektive. – – The debate over abolishing day care fees in Germany is ongoing. Coming from an education and family economics perspective, this contribution summarises various arguments pro and contra different day care fee systems. The following questions are addressed: How much is paid in fees over the entire income distribution? How do fees differ by region and provider? And how would households react if there were no longer any day care fees? In addition to discussing the huge variety of fee systems, other issues which contribute to a very diverse day care system are also briefly described. Overall, more intense federal engagement is needed, which makes sense given the nation-wide benefi ts of a qualitatively high level of day care quality.
Keywords: J13; I2; H5; 330